Immediate impact of healthcare-facility–onset Clostridium difficile laboratory-identified events reporting methodology change on standardized infection ratios. (23rd October 2018) - Figueroa Castro, Carlos E.; Palen, Louis; Johnson, Carrie; Graham, Mary Beth; Letzer, David; Ledeboer, Nathan; Buchan, Blake; Block, Timothy; Seliger, Heather; Singh, Siddhartha; Behrens, Elizabeth; Huerta, Susan; et al.
Abstract: In 2018, the Clostridium difficile LabID event methodology changed so that hospitals doing 2-step tests, nucleic acid amplification test (NAAT) plus enzyme immunofluorescence assay (EIA), had their adjustment modified to EIA-based tests, and only positive final tests (eg, EIA) were counted in the numerator. We report the immediate impact of this methodological change at 3 Milwaukee hospitals.